Multi-site Project Management Ontology Systems Development Methodology - Cheah, Chan; Chang, Elizabeth (IEEE, 2005)
This paper examines how ontology principles can be applied in the design of a semantic web service system for supporting multi-site project management (MSPM) in Industrial Automation. It reports work in progress views of what constitute the MSPM ontology system development methodology,which is currently revealing to be best practice and standards driven.The methodology requires linking conventional SDLC processes with semantic MSPM knowledge standards development and change management, and it fosters the inclusion of semantic knowledge standards (in addition to ICT standards)in governing the design of systems.